How young people describe the impact of living with and beyond a cancer diagnosis: feasibility of using social media as a research method. Issue 11 (8th January 2016) - Gibson, F.; Hibbins, S.; Grew, T.; Morgan, S.; Pearce, S.; Stark, D.; Fern, L. A.
Abstract: Objective: Young people with cancer exhibit unique needs. During a time of normal physical and psychological change, multiple disease and treatment‐related symptoms cause short and long‐term physical and psychosocial effects. Little is known about how young people cope with the impact of cancer and its treatment on daily routines and their strategies to manage the challenges of cancer and treatments. We aimed to determine how young people describe these challenges through a social media site. Methods: Using the principles of virtual ethnography and watching videos on a social media site we gathered data from young people describing their cancer experience. Qualitative content analysis was employed to analyse and interpret the narrative from longitudinal 'video diaries' by 18 young people equating to 156 films and 27 h and 49 min of recording. Themes were described then organized and clustered into typologies grouping commonalities across themes. Results: Four typologies emerged reflective of the cancer trajectory: treatment and relenting side effects, rehabilitation and getting on with life, relapse, facing more treatment and coming to terms with dying. Conclusions: This study confirms the need for young people to strive towards normality and creating a new normal, even where uncertainty prevailed. Strategies young people used to gain mastery over their illness and the types of stories they choose to tell provide the focus of the main narrative. Social Media sites can be examined as a source of data, to supplement or instead of more traditional routes of data collection known to be practically challenging with this population. Copyright © 2016 John Wiley & Sons, Ltd.